Global History with Chinese Characteristics Autocratic States along the Silk Road in the Decline of the Spanish and Qing Empires 1680-1796 - Perez-Garcia, Manuel (Palgrave Studies in Comparative Global History, 2021)
This open access book considers a pivotal era in Chinese history from a global perspective. This book's insight into Chinese and international history offers timely and challenging perspectives on initiatives like "Chinese characteristics", "The New Silk Road" and "One Belt, One Road" in broad historical context. Global History with Chinese Characteristics analyses the feeble state capacity of Qing China questioning the so-called "High Qing" (shèng qīng 盛清) era's economic prosperity as the political system was set into a "power paradox" or "supremacy dilemma". This is a new thesis introduced by the author demonstrating that interventionist states entail weak governance. Macao and Marseille as a new case study aims to compare Mediterranean and South China markets to provide new insights into both modern eras' rising trade networks, non-official institutions and interventionist impulses of autocratic states such as China's Qing and Spain's Bourbon empires.